Biomonitoring–health risk nexus of potentially toxic metals on Cerithidea obtusa: a biomonitoring study from Peninsular Malaysia - Yap, Chee Kong; Al-Mutairi, Khalid Awadh (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
The present study aimed to assess the human health risks of six potentially toxic metals (PTMs) (Cd, Cu, Fe, Ni, Pb and Zn) in 21 populations of popular mangrove snails, Cerithidea obtusa, collected from Malaysia. In general, the concentrations (mg/kg wet weight) of Cd (0.03–2.32), Cu (11.4–35.2), Fe (40.9–759), Ni (0.40–6.14), Pb (0.90–13.4) and Zn (3.11–129) found in the snails in all populations were lower than the prescribed maximum permissible limits (MPL)s for Cd, Cu, Ni, Pb and Zn. However, in the investigated snail populations, Cd (14%), Pb (62%), Cu (19%), and Zn (10%) were found in exceedance of the MPL of the respective metal. The target hazard quotient (THQ) values in all populations for Cu, Ni, Fe and Zn were all found to be below 1.00. However, for the THQ values of Cd and Pb, two populations exceeded 1.00, while others were below the threshold level. The estimated weekly intake (EWI) of all six metals for all populations was only 0.03–4.65% of the provisional tolerable weekly intake. This conclusively indicates that, based on the EWI, there are no health risks of the six PTMs in the consumption of snails from Malaysia since the assessments are dependent on the consumers’ body weight and consumption rate. Nonetheless, the present results indicate that the amounts of snails consumed should be limited to minimize the potential health risks of PTMs to consumers. The relatively low and weak but positive correlations of Cu, Ni, Pb and Zn between C. obtusa and their habitat sediments indicate that C. obtusa can be a potential biomonitor for Cu, Ni, Pb and Zn. This is important for effective mangrove management from the perspective of the sustainable resources from the intertidal mangrove environment. Hence, the biomonitoring–health risk nexus of PTMs in mangrove snails is proposed in the present study.